PERAN EDUKATIF GURU AKIDAH AKHLAK DALAM PENGEMBANGAN KECERDASAN SPRITUAL PADA SISWA MADRASAH TSANAWIYAH NEGERI 1 KOTA JAMBI - Hamdi, Muhammad; Idarianty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the educational role of Akidah Akhlak teachers in developing the spiritual intelligence of students in class VIII A at Madrasah Tsanawiyah Negeri 1 Kota Jambi and to identify the supporting and inhibiting factors influencing this process. The background of this research is the fact that several students still show low spiritual awareness, such as lack of responsibility, limited understanding of spiritual intelligence, and low motivation in practicing religious values in daily life. This research uses a qualitative descriptive approach with a field research design. Data were collected through observation, interviews, and documentation involving Akidah Akhlak teachers, the school principal, and students as research subjects. The results show that the educational role of Akidah Akhlak teachers is carried out through guidance, role modeling (uswah hasanah), motivation, and the internalization of Islamic values in the learning process. Teachers not only deliver cognitive knowledge but also cultivate spiritual values through worship habituation, character building, and meaningful learning activities. The development of students’ spiritual intelligence can be seen in increased religious awareness, moral responsibility, self-control, and positive attitudes in everyday life. Supporting factors include a religious school environment, school programs, and student motivation, while inhibiting factors include differences in family background and social environmental influences